Comparison of Ruang Guru and Primagama Promotion Strategies in Attracting Consumers - Clarissa Aulia; Vina Gabriella Saragih (Jurnal Manajemen Bisnis dan Pariwisata, 2025)
Promotional strategies are an important element in attracting consumer interest, especially in the education service sector such as tutoring institutions. This study aims to see and compare the promotion methods used by Ruangguru and Primagama. The main focus is on the type of promotional content, the communication style, the target market, and how effective the promotion is in attracting the attention of potential consumers. This study uses a descriptive qualitative method, with data collected through social media observations, interviews, and literature studies. The results of the study show that Ruangguru excels in using interactive digital promotions, such as the Clash of Champions program that is viral on social media and a delivery style that is suitable for the younger generation (Gen Z). Meanwhile, Primagama still relies on conventional promotional methods, such as distributing brochures, collaborating with schools, and direct promotion at branches. The AIDA method was used to analyze the effectiveness of promotions, and the results showed that Ruangguru excelled at all stages, while Primagama was stronger at the Passion and Action stages. This difference in approach shows that each institution has its own way of understanding the market and the needs of its consumers.